1993
DOI: 10.1021/ic00057a012
|View full text |Cite
|
Sign up to set email alerts
|

A molecular orbital comparison of molybdenum-sulfur dimers with sulfido ligands bridged by CH2 and FeCp fragments

Abstract: An extensive reactivity with hydrogen and unsaturated molecules has been characterized for the /t-sulfide ligands in (CpMo)2(M-S)2S2CH2 (2). However, the bridging disulfide ligand in the heteronuclear cluster [(CpMo)2(M-S2)(M-S2FeCp)]+ (3) was not reactive toward hydrogen or olefins. Extended Huckel molecular orbital calculations have been carried out for 2 and for the hypothetical Fe-Mo cluster with bridging sulfides rather than a disulfide ligand [(CpMo)2(/t-S)2(S2FeCp)]+ (3'). The electronic structures of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Although a M−M‘ bonding interaction cannot be assigned solely on the basis of distance, the asymmetry, which does not appear to be a result of packing forces, suggests that there may be a weak bonding interaction between Cu and Mo(2). The distance is similar to previously reported Cu−Mo distances in mixed-metal M 4 S 4 cubane and M 3 S 3 incomplete cubane structures. , Examples of Mo−M‘ bonding interactions have been observed previously for clusters derived from the Mo 2 S 4 core, and extended Huckel calculations have provided a bonding description for one such system …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although a M−M‘ bonding interaction cannot be assigned solely on the basis of distance, the asymmetry, which does not appear to be a result of packing forces, suggests that there may be a weak bonding interaction between Cu and Mo(2). The distance is similar to previously reported Cu−Mo distances in mixed-metal M 4 S 4 cubane and M 3 S 3 incomplete cubane structures. , Examples of Mo−M‘ bonding interactions have been observed previously for clusters derived from the Mo 2 S 4 core, and extended Huckel calculations have provided a bonding description for one such system …”
Section: Resultssupporting
confidence: 89%
“…Although the reactivity of the dinuclear methanedithiolate-bridged derivatives of molybdenum has been extensively studied, a crystal structure of one of these derivatives has not been reported previously. Previous molecular orbital calculations on this complex (unsubstituted Cp ligand) indicated that the extensive sulfur-based reactivity observed for the structure was consistent with the presence of two bridging sulfido atoms rather than a μ 2 −η 2 disulfido ligand . The calculations also indicated that there was an antibonding interaction between these two bridging ligands.…”
Section: Resultsmentioning
confidence: 62%
“…[3][4][5] Investigations of these homogeneous Mo 2 S 4 complexes cover a broad range of topics, including catalysis and electrocatalysis, [6][7][8][9][10][11] a wide variety of bond forming reactions, [12][13][14][15][16][17][18][19] free radical reactivity, [20][21][22][23][24] photolytic reactions, 25 and the preparation of heterometallic sulfide clusters. [26][27][28][29][30][31] In spite of the importance of molybdenum sulfide chemistry and the extensive research into Mo 2 S 4 complexes, very few S-H bond energies have been determined for MoS-H bonds, 6,32 homogeneous and heterogeneous catalysis of hydrogen transfer pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous Mo 2 S 4 complexes have been widely studied as a result of the prevalence of molybdenum sulfides in both hydrogenation and hydrodesulfurization (HDS) catalysts and enzymes. Investigations of these homogeneous Mo 2 S 4 complexes cover a broad range of topics, including catalysis and electrocatalysis, a wide variety of bond forming reactions, free radical reactivity, photolytic reactions, and the preparation of heterometallic sulfide clusters. In spite of the importance of molybdenum sulfide chemistry and the extensive research into Mo 2 S 4 complexes, very few S−H bond energies have been determined for MoS−H bonds, , even though they are key to a fundamental understanding of homogeneous and heterogeneous catalysis of hydrogen transfer pathways.…”
Section: Introductionmentioning
confidence: 99%